A comparative study on microstructure and mechanical properties near interface for dissimilar materials during conventional V-groove and narrow gap welding. (January 2017) - Nivas, R.; Singh, P.K.; Das, G.; Das, S.K.; Kumar, S.; Mahato, B.; Sivaprasad, K.; Ghosh, M.
Graphical abstract: Highlights: Low alloy steel and 304LN stainless steel was joined by conventional V-groove welding and narrow gap welding. In both welds IN82 was used as consumable. Comparing with existing literature reports, unique aspects of the manuscript may be described as: Detail exploration and explaining microstructural changes across the fusion boundary between LAS and Ni-base alloy using different characterisation techniques like microscopy and X-ray diffraction. Understanding the sequence of deformation and identifying the weakest region across fusion boundary through in-situ tensile test; this was complimented to micro-hardness profile to endorse the inference. Evaluation of work hardening behaviour near FB-1 during plastic deformation under uni-axial loading for a highly heterogeneous assembly. Co-relation between microstructure and mechanical properties. Abstract: Low alloy steel and 304 LN austenitic stainless steel pipes were welded together by gas tungsten arc and narrow gap welding. The aim of investigation was to identify particular welding technique, which may able to deliver better joint quality over the other considering mechanical properties of assemblies. Welding consumable was IN82 for both of them. Multilayered buttering was done over low alloy steel prior to welding for conventional GTAW. Microstructural characterisation was done and tensile strength was determined through in-situ deformation of miniature samples for welded joints. Low alloy steel consisted of heat affected zone close to interface. Near fusion boundary between low alloy steel and IN82, islands of martensite, complex alloy carbides, Types-I and II boundaries were formed. Width of heat affected zone and martensite layer was more for conventional welding in comparison to narrow gap welding. During in-situ tensile testing crack was initiated from stress concentration site and propagated through IN82. Joint strength and strain hardening co-efficient for narrow gap welded specimen was higher than conventional welded sample. This indicated better formability of narrow gap welded assembly with respect to gas tungsten arc welded specimen.